The Interpretation of Religion and Early Marriage Practices in Cirebon Regency: The Perspective of Nahdlatul Ulama (NU) Scholars in the Context of State Law and Socio-Cultural Aspects - Kholik , Abdul; Khosyi'ah , Siah; Saepullah , Usep; shaleh , Chaerul (Journal of Posthumanism, 2025)
Child marriage is a complex social issue in Indonesia, particularly within the Nahdlatul Ulama (NU) community. This study aims to understand how religious, social, and economic perspectives influence the practice of early marriage in Cirebon Regency, focusing on the viewpoint of NU scholars. Using a phenomenological approach, this research analyzes the subjective experiences of scholars involved in the practice of child marriage. The main findings reveal that although state law sets the minimum marriage age at 19, the more flexible religious interpretation regarding physical and mental maturity (aqil baligh) dominates the views of the scholars. Social and economic factors also play a significant role, with early marriage often seen as a solution to reduce financial and social burdens. This study highlights the tension between state law and social and religious norms in determining the legal age for marriage. The implications of these findings suggest that a more inclusive policy approach, considering local religious and social values, is necessary to reduce the practice of early marriage in Indonesia.